Exogenous insulin antibody syndrome treated with plasma exchange after an incomplete response to immunosuppressive therapy. Issue 4 (20th May 2021) - Zhuang, Yuan; Wei, Xudong; Yu, Yang; Wang, Deqing
Abstract: A 43‐year‐old man with a 23‐year history of type II diabetes presented with uncontrolled hyperglycemia with frequent episodes of ketoacidosis. He was diagnosed with exogenous insulin antibody syndrome, and received high‐dose methylprednisolone to treat insulin resistance. Ketoacidosis relapsed 2 years later, and the patient showed an incomplete response to glucocorticoids. We decided to administer therapeutic plasma exchange, which resulted in rapid lowering of the daily insulin requirement and improved glycemic control.